Open-Source Speech Corpus and Initial Speech Recognition Experiments - A.A. Rakhmanov (Research Parks Publishers, 2022)
We present a speech corpus and report preliminary results of automatic speech recognition (ASR) using a hidden deep neural network Markov model (DNNHMM) and an end-to-end (E2E) architecture.